El comensal de Gabriela Ybarra : le creux mémoriel comme lieu de (re)construction du passé - Marion Billard (Amnis)
The long process of dissolution of the terrorist organisation Euskadi Ta Askatasuna (ETA), which ended in May 2018, put an end to more than fifty years of regular terrorist attacks committed in Spain and France. Thus, several generations have been directly or indirectly affected by this violence. In the last few years, one can observe a rise of cultural productions evoking this mortal presence in order to preserve its memory. This is the case whithin Gabriela Ybarra's novel, entitled The Diner Guest, published in 2015. Indeed, in this novel, she deals with the abduction and the murder of her paternal grandfather, Javier de Ybarra y Bergé, by the ETA in 1977. In order to narrate this event which she didn’t experience, G. Ybarra combines individual memories (personal and familial) and collective memories (journalistic, social and literary) and she also uses fiction. The analysis of a novel from a granddaughter of a mortal victim of the ETA will therefore allow to put an emphasis on the existing interactions between memory and post-memory (M. Hirsch), which themselves determine the modalities of the narrative form of the traumatic past author’s along with the Spanish society.